# Algebra

Solve Q= (N-S)/ N for N

So when I multiply both sides by N
I get Q(N)= N-S
I know I am doing something wrong, the answer is in the book which is
N=S/(1-Q)but I don't understand were the 1 comes from. Could you write it out step by step, so I can see what I don't yet understand?

Here's one way to solve for N.

Q = (N - S)/N

Factor out N in the numerator:

Q = N(1 - S/N)/N

Cancel out N in both numerator and denominator to end up with this:

Q = 1 - S/N

Subtract 1 from both sides:

Q - 1 = - S/N

Multiply both sides by N:

N(Q - 1) = - S

Divide both sides by (Q - 1):

N = - S/(Q - 1)

Factor out -1 to end up with this:

N = S / (1 - Q)

I hope this will help.

thanks, I would have never gotten that far. I didn't know that the N could be factored out like that- to get 1, so with this knowledge I try other problems and see if it works out for me.

1. 👍
2. 👎
3. 👁

## Similar Questions

1. ### Math

A student is trying to solve the set of two equations given below: Equation A: x + z = 6 Equation B: 2x + 4z = 1 Which of the following is a possible step used in eliminating the z-term? Multiply equation B by 4. Multiply equation

2. ### simultaneous equations

Solve 2a + b = 3 4a - 5b = 20 My attempt Multiply the first equation by 5 So, 10a + 5b = 15 4a - 5b = 20 Add them together 14a = 35 Divide both sides by 14 a = 2.5 Substitute (I have done it with the second one) 10 - 5b = 20 Take

3. ### math

A=1/2h (b1 + b2) Solve for b1 A=1/2h (b1 + b2) Solve for b1 I assume this is A = (1/2)(h)(b1 + b2); i.e., the h is in the numerator and not the denominator Multiply both sides by 2. 2A = (2*1/2)h(b1 + b2). 2*1/2 on the right side

4. ### algebra

Which could be a first step in solving the equation 1/4x+1/2=3/4x in an efficient way? Select two answers. A.multiply by 4 on both sides B.multiply by 2x on both sides C.subtract 1/4x from both sides D.add 1/2 to both sides plz

1. ### Algebra

The first step to solve for y in y/3= 6 + x is A) to subtract x from both sides of the equation. B) to subtract y/3 from both sides of the equation. C) to divide each term on both sides of the equation by 3. ******* D) to multiply

2. ### PLEASE HELP ME!!!

What is the first step in solving the problem, 3x-8/12=9? A) Add 8 to both sides. B) Multiply by 12 on both sides. C) Divide by 3 on both sides. D) Subtract 9 on both sides.

3. ### Pre Cal.--Check my work?

Solve the system of equations: x - y - z = 2; x + 2y - 2z = 3; 3x - 2y - 4z = 5? well, you have: 1- x-y-z=2 2- x+2y-2z=3 3- 3x-2y-4z=5 multiply both sides of the equation 1 by 2: x-y-z=2 ===> 2x-2y-2z=4 add this by equation 2:

4. ### MATH

1. 4-2 Add 5 to both sides, then add 3, then add (-4) 3. -4

1. ### Precalculus

This is for solving exponential/logarithmic functions: (This is a base e Logarithmic function I would assume): e^(4x)/10 =4^x-2 ? I understand the properties of logs for the most part, but I have a hard time figuring out the

2. ### Algebra

Which of the following describes a correct method for solving the equation below? -7/2n + 5 = -16 1. add 5 to both sides, then divide both sides by 2/7 2. subtract 5 from both sides, then multiply both sides by -7/2 3. add -5 to

3. ### math,help

I need help with thisone solve: ((x)/(5x+10))+ ((x-3)/(x+2)) = (7)/(5) Let's take that first part: (x)/(5x+10) In the denominator, factor out "5" That leaves that part as: x/(5(x+2)) So now we have: ((x)/5(x+2)) + ((x-3)/(x+2)) =

4. ### Formulas and Literal Equations

Have not a clue please help to figure this one out: P-Q=-R, for Q Do you wish to solve for Q? If so, subtract P from both sides. P-P-Q=-R-P Combine terms. -Q=-R-P Multiply by -1 Q = R+P